Development of a Surveillance Model to Prevent Injury for All Age Groups Based on the Participation of Communities in the Sub-District Health Promoting Hospital Devolution in Ubon Ratchathani Province - Sansiritawisuk, Getsara; หวานคำ จันทร์เพ็ญ; บุตรกาล ชัยนันต์; สมหมาย มนศภรณ์; นริษทิ์ภูวพงษ์ ภูมิพัฒน์; ผลเกิด จุติพร (Journal of Health Science of Thailand, 2025)
This research aims for Development of a Surveillance model to prevent injury for all age groups based on the Participation of Communities in the Sub-District Health Promoting Hospital Devolution in Health Region 10. The studied area is Nong Bok, Lao Sue Kok, Ubon Ratchathani during October 2023 – February 2024. The studied group is comprised of Public Personnel, Private Personnel, and target population that are involved and voluntary in participation to be Surveillance Network which includes 148 people and the target group to be surveillance are those who are at risk of getting injured in all age groups which include 7,821 people. The tools are the surveillance system that the researchers have developed with the collaboration of the locals. The data analysis is conducted through qualitative methods with content and quantitative analysis by descriptive studies McNemar c2 and Paired t-test The results show the Model of injury surveillance “Nong Bok Aware and Care for Injury” which contains (1) Integration of the work of Surveillance Network for all age groups (2) The design of the tools used in collaborated surveillance (3) The creation of the mechanics that propels for continuous surveillance system (4) the management of the risk for all age groups and the result of the surveillance is the information that can be used in warning and problem solving that causes the change in decreasing the risk factors from the injury that can be commonly found for all age groups including individuals, causes, and environment that are statistically significant at P-value < 0.01. In terms of the knowledge in prevention and solving the problem of injury from the risk group of all age groups, the researchers found that it increases by statistical significance at P-value < 0.01 and it reduces its effects which are the injury rate for all age groups decreasing from the median from previous five years when compared to the same duration. Thus, Developing the collaboration in supervision from family and communities and increasing the knowledge of supervisor in both children and seniors and risk group along with creating Surveillance Network to avoid injury that are effective and able to reduce the injury rate and makes the model area in working on injury prevention for all age groups. Keywords: Injury, developing surveillance system, Devolution